ANALISIS MANAJEMEN SDM UNTUK PENINGKATAN KINERJA GURU SMK PADA ASPEK LITERASI DIGITAL - Arrori Ashar Hidayad; Lathifaturrohmah; Luthfiyah Nurlaela; Achmad Imam Agung (CV. Adiba Aisha Amira, 2025)
This study aims to analyze Human Resource (HR) management in an effort to improve the performance of vocational high school teachers in Bojonegoro Regency, especially in the aspect of digital literacy. The main problems raised are the low digital competence of teachers in facing the demands of industry 4.0, rapid technological developments, and the need for digital-based curriculum implementation. The research method uses a descriptive qualitative approach with data collection techniques through in-depth interviews, field observations, and document analysis at the Bojonegoro Regional Education Office Branch. The results of the study show that teacher HR management has been implemented through digital literacy training programs (journalism schools, cloud computing training, and anti-hoax workshops), direct coaching by the head of the office, and collaboration between institutions. However, there are challenges such as uneven distribution of teachers, limited budget, and difficulties in adapting to the Merdeka Curriculum. The program evaluation shows an increase in teacher skills in utilizing technology, although continuous improvement is needed to overcome structural barriers. This study recommends strengthening technology-based training, equalizing resources, and increasing collaboration with the industrial world to ensure the relevance of education to the needs of the digital era.